The Impact of China’s Illegal Same-sex Marriage System on Homosexuality - Zhang, Ziyue (Transactions on Social Science, Education and Humanities Research, 2024)
Influenced by history and culture, China attaches great importance to collective interests, and the concept of "following the trend" is deeply embedded in the thinking patterns of every generation. Therefore, Chinese people are prone to develop non social pattern bias aversion. As a minority group, the LGBTQ+community undoubtedly contradicts China’s deep-rooted traditional family model in terms of sexual orientation. This behavior pattern that does not conform to the “trend” is easily perceived by those who follow the "man-woman" family model as "breaking the rules", leading to disgust towards the LGBTQ+community. This disgust has always deepened society’s prejudice against homosexuals. And this prejudice keeps the LGBTQ+community under pressure from various external parties, causing them to be naturally marginalized by society and facing various difficulties in their lives. In order to better protect the rights and interests of the LGBTQ+community, this article will point out the current dilemma of the LGBTQ+community in China,analyzing the relationship between this dilemma and the illegality of same-sex marriage in China.